2013
DOI: 10.1080/03057070.2013.858541
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance and the City: Patronage, Power-Sharing and the Politics of Urban Control in Zimbabwe

Abstract: Surveillance and the city: patronage, power-sharing and the politics of urban control in Zimbabwe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 6 publications
0
43
0
Order By: Relevance
“…The urban water supply mandate for municipalities has been given back to local authorities. This chaos within the urban water sector, most scholars argue, was a manifestation of the contestation of the social, economic and political nature of water in Zimbabwe's urban spaces (Kamete, 2012;McGregor, 2013;Musemwa, 2014;Terence, 2007). Chabal (2009) argues that once there is structure, agency can then be used for purposeful social action within the defined social structure.…”
Section: Chabal's Thesis and Water Reform In Zimbabwementioning
confidence: 96%
“…The urban water supply mandate for municipalities has been given back to local authorities. This chaos within the urban water sector, most scholars argue, was a manifestation of the contestation of the social, economic and political nature of water in Zimbabwe's urban spaces (Kamete, 2012;McGregor, 2013;Musemwa, 2014;Terence, 2007). Chabal (2009) argues that once there is structure, agency can then be used for purposeful social action within the defined social structure.…”
Section: Chabal's Thesis and Water Reform In Zimbabwementioning
confidence: 96%
“…and Zanu-PF, which led to the latter radically intervening in urban affairs (Kamete, 2006;McGregor, 2013;Ranger, 2007). For civil society and non-governmental organisations, state repression at local government level and contentious politics make it difficult to engage, protect and promote the rights and interests of residents (Kamete, 2009).…”
Section: Slum Upgrading In Hararementioning
confidence: 98%
“…The Dumba Report catalogues a series of land allocations to an array of briefcase and shelf companies — what McGregor (: 793) terms ‘disreputable companies'. But no detailed attention was given to ‘reputable companies' such as the Commercial Bank of Zimbabwe (CBZ), the largest local bank in the country, which is mentioned only in passing in the report.…”
Section: The Commercial Bank Of Zimbabwe ‘Banks' the ‘People's Market'mentioning
confidence: 99%
“…McGregor (: 784) correctly observed that the period of Zimbabwe's Inclusive Government (IG) from 2009 to 2013 — in which the ruling ‘revolutionary' liberation nationalist party, the Zimbabwe African National Union–Patriotic Front (ZANU–PF), shared power with the neoliberal opposition Movement for Democratic Party (MDC) — ‘opened up limited new political space' to contest ZANU–PF hegemony and to expose corruption and partisan practices, especially within urban councils. Since 2000, like most ruling parties in Africa, ZANU–PF has consistently lost the urban vote to the MDC, which now controls all major councils (Mbiba and Ndubiwa, : 90; McGregor : 784). However, ZANU–PF's control of the state and central government enabled it to sustain its vice grip on urban local authorities through, inter alia , the machinations of Dr Ignatius Chombo, then Minister of Local Government, Rural and Urban Development (McGregor, ; The Source , ).…”
Section: Introduction: Political and Institutional Settingsmentioning
confidence: 99%
See 1 more Smart Citation